The nature of cold gas in the Chamaeleon molecular cloud complex - Arias Toctaguano, Daniel Sebastian (2025)
The gas content of the Milky Way has been typically studied through observations of carbon monoxide (CO) and neutral atomic hydrogen (H i) spectral lines. However, when we compare the column density measurements from these data sets with those from gamma ray observations, we find an apparent discrepancy indicating the presence of large amounts of unidentified gas. This gas is also referred to as the dark neutral medium (DNM). It is likely a combination of cold H i and molecular hydrogen, both of which are difficult to observe directly. The goal of the thesis is to determine the fraction of the DNM in the Chamaeleon region that is cold H i, based on H i emission and absorption data, and to characterize the physical properties of the H i gas in this region. We find that the average spin temperature around the molecular cloud is ∼ 50 K, denoting the presence of cold H i. In addition, the H i composes ∼ 60 % of the DNM in most of the positions studied in the Chamaeleon molecular cloud complex, making it the dominant component of the DNM in the Chamaeleon region.